Exact algorithms for the satellite image selection problem - Swat, Sylwester; Antczak, Maciej; Zok, Tomasz; Blazewicz, Jacek; Musiał, Jędrzej (Zielona Góra: Uniwersytet Zielonogórski)
Space development is more relevant than ever with the increasing number of satellite launches for various applications. The amount of space data collected daily is growing exponentially and many customers are interested in continuously monitoring different regions of the Earth. It often requires stitching together many images from other providers to cover an Area of Interest (AOI), resulting in a mosaic. Each satellite image has various parameters, such as cost, download time, cloud coverage, and resolution.
Keywords: satellite image mosaic selection; set cover; hitting set; plane division